On the Connection between Deutsch-Jozsa Algorithm and Bent Functions - Marinho, Eraldo Pereira [UNESP] (IOP Publishing, 2021)
It is presently shown that the Deutsch-Jozsa algorithm is connected to the concept of bent function. Particularly, it is noticeable that the quantum circuit used to denote the well-known quantum algorithm is by itself the quantum computer that performs the Walsh transform of a Boolean function. Consequently, the output from the Deutsch-Jozsa algorithm when the hidden function is bent corresponds to a flat spectrum of quantum states.